Utilization of growth monitoring and promotion services and associated factors among under two years of age children in Southern Ethiopia - Feleke, Fentaw Wassie (PLoS One, 2017)
Growth monitoring and promotion (GMP) is a prevention activity comprised of growth monitoring (GM) linked with promotion that serves as the core activity in an integrated child health and nutrition program. However, different methods of institutional studies have shown that utilization of GM services has remained to be inadequate. There is scarcity of studies conducted about GMP in quantitative method. Therefore, this study was conducted to address the proportion of GMP services and associated factors among children under two years of age in rural communities of Mareka district, Southern Ethiopia. Community based cross-sectional survey was conducted from August to September 2015. Single population proportion formula was used to determine the sample size with multi stage sampling technique. A total of 819 children under two years of age were included. Pretest was done on 10% of the total sample size. Data were analyzed using SPSS version 20.0 software. Bivariate and multivariate logistic regressions used to analyze data. The response rate was 95%. Utilization of GMP services was 16.9%. Institutional delivery AOR (95% CI): 3.01(1.65–5.50), index child age 12–17 months AOR (95% CI): 4.03(2.16–7.51) and 18–23 months AOR (95% CI): 3.08(1.70–5.57), family size 4–5 AOR(95% CI): 0.14(0.06–0.33), family size >5 AOR(95% CI): 0.34(0.14–0.82), regular GMP attendance AOR (95% CI): 4.37(2.45–7.80), medium wealth index AOR(95% CI): 3.14(1.51–6.52) and high wealth index AOR(95% CI): 3.24(1.59–6.62) were factors associated with utilization of GMP services. Utilization of GMP services was low. Thus, efforts should be made to improve utilization of GMP services through promotion of institutional delivery, different family planning methods, and regular GMP attendance.